Effect of Lactobacillus casei and Lactobacillus acidophilus in laying hens challenged by Escherichia coli infection - Lokapirnasari, Widya Paramita; Sahidu, Adriana Monica; Maslachah, Lilik; Sabdoningrum, Emy Koestanti; Yulianto, Andreas Berny (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aimed to prove the potential of Lactobacillus casei and Lactobacillus acidophilus probiotics as alternative substitutes of antibiotic growth promoters in laying hens challenged by Escherichia coli infection in order to enhance their growth performance and hen day production. The study used a total of 120 laying hens aged 25 weeks, divided into 3×2 treatments with each comprising 4 replications, and each replication consisted of 5 hens. The study used a completely randomised factorial design; factor a was the feed additive (control, antibiotics growth promoters /AGP, probiotic), whereas factor b was the E. coli infection (non-infection and E. coli infection). The results showed that there were significant differences (p<0.05) between the treatment of feed additive (factor a), and E. coli infection (factor b), and interaction (p<0.05) between the feed and the infection for the egg weight, hen day production, feed conversion ratio and feed efficiency. The probiotic use of 0.5% L. casei + 0.5% L. acidophilus in hens either infected or uninfected with E. coli still produced the highest egg weight, hen day production, feed efficiency and reduced feed conversion ratio compared to all treatments. Based on the results, it can be concluded that the use of probiotics 0.5% L. casei and 0.5% L. acidophilus act as alternative substitutes for antibiotic growth promoters in laying hens challenged by E. coli infection.